Prehľad o peňažných tokoch - cash flow - Czillingová, Jana (Univerzita Pardubice, 1998)
The contemporary liquidity is one of the essential tasks of every enterpreneurship. The liquid ability in the future is quaranted by the balance between future incomes and costs. The cash flow as a flow unit enablesn the complex description and evoluation of the financial position of the company and by this way it decides about the payment ability and liquidity of a company.
Keywords: peněžní toky; Cash flow; likvidita; zisk